Palaeolithic paint palettes used at La Garma Cave (Cantabria, Spain) investigated by means of combined in situ and synchrotron X-ray analytical methods. Issue 3 (9th February 2015) - Gay, M.; Alfeld, M.; Menu, M.; Laval, E.; Arias, P.; Ontañón, R.; Reiche, I.
Abstract : This rock art study of La Garma provides new and original insights into the characterisation of the prehistoric paint palette. Abstract : La Garma Cave is part of the most exceptional Palaeolithic sites discovered at the end of the 20 th century in the North of Spain and was included by UNESCO in the World Heritage List in 2008. This cave contains more than 500 exceptional Palaeolithic graphical units, some of them linked to the Magdalenian floors. La Garma Cave was never opened to the public and thus provides a closed karst system with untouched archaeological surfaces, conferring to it an important position in the study of the Upper Palaeolithic in this region. A combined analytical strategy was chosen to enhance the understanding of the rock art distribution in this cave, looking for different decorative steps. SEM-EDX analysis carried out on fifty-six samples was complemented by μXRF and μXANES measurements at the Fe K-edge at the Deutsches Elektronen-Synchrotron DESY (Hamburg, Germany). A systematic study of the prehistoric representations on-site has been initiated with portable XRF instruments. The new data acquired by the combination of synchrotron radiation methods and the first in situ measurements in the cave provide more detailed insights into the characterisation of the pictorial matters used by the prehistoric artists. Data evaluation was performed using principal component analyses. It offers arguments to link specific pictorial properties to particular periods of ornamentation inside the cave.